Multidrug resistance and extended spectrumbetalactamase producing strains causing lower respiratory tract and urinary tract infection - Pokhrel, BM; Koirala, J; Mishra, SK; Dahal, RK; Khadga, P; Tuladhar, NR (Journal of Institute of Medicine Nepal, 2007)
Background: Multidrug resistance (MDR) and Extended spectrumbeta-lactamase (ESBL) producing strains are becoming world-wide problem. With a view to determine prevalence of MDR and ESBL strains causing lower respiratory tract infection (LRTI) and urinary tract infection (UTI), a pilot study was conducted in Microbiology Laboratory of TUTH from April-September 2004. Material and Methods: Sputum and urine samples were collected, cultured and the bacterial isolates were identified with the use of standard method as described by American Society for Microbiology. These bacterial isolates were then subjected for antibiotics-sensitivity test with the use of disc diffusion method as described by Kirby Bauer. ESBL production was tested as described by National Committee for Clinical Laboratory Standards (NCCLS). Results: Of the total bacterial isolates from sputum samples, 47.57% were MDR. The ESBL producing isolates were 24.27%. In case of urinary isolates, 60.40% and 16.00%. were found to be MDR and ESBL respectively. Conclusion: These strains should be subjected for genetic study to acquire their detail genetic make-up to characterize the mechanism of drug resistance. This type of study should be continued throughout the year in order to acquire exact status of MDR and ESBL in Nepal. Key Words: MDR, ESBL, LRTI, UTI The full text of this paper is available at Journal of Institute of Medicine website